Echocardiographic Outflow Pump Ramp Test in Centrifugal-Flow Left Ventricular Assist Device. Issue 3 (March 2017) - lacovoni, Attilio; Vittori, Claudia; Fontana, Alessandra; Carobbio, Alessandra; Fino, Carlo; D'Elia, Emilia; Terzi, Amedeo; Senni, Michele
This study sought to develop a novel echocardiogram outflow ramp test to detect device malfunctions in centrifugal-flow left ventricular assist devices (LVADs). This new ramp pump test is based on the direct analyses of systolic and diastolic ratio (S/D) Doppler velocity in the outflow cannula in the HeartWare LVAD during progressive increases in speed. The results showed that in patients with normal pump function, the Doppler velocity S/D ratio gradually decreased during LVAD speed increases. This test is easily performed and seems promising to detect normal pump function in patients assisted by a centrifugal flow LVAD.